Acute Screening for PTSD Among Child Earthquake Survivors in Palu, Sulawesi, Indonesia - Ahmad,; Marzo,; mt, Win; R, Bahari; NA, Ghaffar; N, Amlasi (International Journal of Psychosocial Rehabilitation, 2020)
Background: Post-traumatic stress disorder (PTSD) is one of the most common neuropsychiatric disorders that may develop followingtraumatic lifeevents (Chiba, 2019). This study is an acute screening for Post-Traumatic Symptoms among children who survivedthe 2018earthquake and subsequent tsunami and soil liquefaction in Palu, Sulawesi, Indonesia. These events werenotable, as they were among the worst disasters in the world and caused massive deaths and destruction in the region.Objectives: The general objective of this study was to determine whether child earthquake survivors inPalu are affected by PTSD. This study also specifically focused on the age, gender, and ethnic group of the children earthquake survivors in the different areas of Kayumalue and JonoOgeto determine if any relationship exists with post-traumatic symptoms.Methods:A cross-sectional survey was conducted in the affected areas in Kayumalue and JonoOge. Data were collected from 69 children who were affected by the earthquake. The PTSS-10 scale, which isa structured questionnaire consisting of 10 close-ended questions, was used for this study. Correlation of the post-traumatic symptoms scores with age, gender, and the ethnic tribe was also analyzed.Results: Atotal of 69 children (26 boys and 43 girls) with a mean age of 10.2 years and are from different ethnic tribesinKayumalue and JonoOge participated in this study. The majority (81.2%) showed no obvious post-traumatic symptoms.Some of the children (11.6%) showed borderline post-traumatic symptoms,whilea few (7.2%) displayedsignificant post-traumatic symptoms.Among the two areas the researchers studied, the child survivors in Kayumaluedid not exhibit obvious signsof PTSD, while the children survivors in JonoOgeshowed significant effects of PTSD (significant up to p